Getting personal about skin: Realizing precision medicine in dermatology. Issue 5 (27th October 2021) - Brownstone, Nicholas; Wu, Jashin J.; Strober, Bruce E.; Dickerson, Tobin J.
Abstract: With the massive influx of data from "omics" methods combined with sophisticated informatics platforms, personalized medicine, defined as the tailoring of medical decision‐making and/or treatments to an individual patient, has led to the promise of better and more efficient patient care. As a concept, personalized medicine could fundamentally alter how clinicians think about the diagnosis and treatment of disease. The introduction of a precision medicine tool has benefits for multiple stakeholders; patients benefit by having improved outcomes, physicians can make confident decisions in managing their patients, and the healthcare system saves significant dollars through the reduction of wasted spend. This paradigm has been particularly true in oncology where biomarker‐driven treatment paradigms have become increasingly common. In this review, personalized medicine and biomarkers in the field of dermatology are reviewed. Specifically, three disease states are discussed including psoriasis, atopic dermatitis, and melanoma. For each disease state, biomarkers and personalized medicine tests are reviewed focusing on diagnosis and treatment for these conditions. The ethics, implementation, advantages, and disadvantages are discussed for the adaptation of personalized medicine in clinical dermatology. The advent of personalized medicine in dermatology could lead to a paradigm shift in how patients are treated, with the resulting improved clinical outcomes leading to concomitant reductions in wasted healthcare expenditures.